Active prospective surveillance study with post-discharge surveillance of surgical site infections in Cambodia. Issue 3 (May 2015) - Guerra, José; Guichon, Céline; Isnard, Margaux; So, Saphy; Chan, Sophors; Couraud, Sébastien; Duong, Bunn
Summary: Barriers to the implementation of the Centers for Disease Control and Prevention (CDC) guidelines for surgical site infection (SSI) surveillance have been described in resource-limited settings. This study aimed to estimate the SSI incidence rate in a Cambodian hospital and to compare different modalities of SSI surveillance. We performed an active prospective study with post-discharge surveillance. During the hospital stay, trained surveyors collected the CDC criteria to identify SSI by direct examination of the surgical site. After discharge, a card was given to each included patient to be presented to all practitioners examining the surgical site. Among 167 patients, direct examination of the surgical site identified a cumulative incidence rate of 14 infections per 100 patients. An independent review of medical charts presented a sensitivity of 16%. The sensitivity of the purulent drainage criterion to detect SSIs was 83%. After hospital discharge, 87% of the patients provided follow-up data, and nine purulent drainages were reported by a practitioner (cumulative incidence rate: 20%). Overall, the incidence rate was dependent on the surveillance modalities. The review of medical charts to identify SSIs during hospitalization was not effective; the use of a follow-up card with phone calls for post-discharge surveillance was effective.